Telegram - Citrine, Walter, 1887-1983
022_0020-001 Liverpool St Victoria F POST OFFICE OVERSEAS TELEGRAM. The Library Central Hall Westminster 1087 PARIS 23893 38 18 1125- TEWSON TRADUNIC S O WEST LONDON - INTERNATIONAL CONFERENCE FIXED 10 AND 11 MARCH STOP CONSULT MIDDLETON AND ARRANGE HALL NEAR WESTMINSTER IF POSSIBLE OR HOLBURN RESTAURANT APPROXIMATELY 200 DELEGATES STOP PHONE TODAY CEGETE SOON AS ARRANGEMENTS MADE - CITRINE - 292/946/22/19